The Relationship of Basic Psychological Needs, Academic Motivation and Alienation from Study of Students in Higher Education - Pulyaeva V.N. (Психологическая наука и образование, 2020)
Academic motivation is one of the most important aspects related to the learning process at the university, as it largely determines the future prospects of self-development and self-realization of young specialists. This issue is also important for educational organizations, because, knowing the specifics of the educational motivation of their students, they will be able to adjust the educational process. The article examines three main components that are associated with the success of studding: basic psychological needs, academic motivation and alienation from study. In the study (N = 1326) there are also differences associated with these components among students who study at the university’s bachelor and master programs. At the first stage of data processing, a comparison was made of these components among undergraduate and graduate students. As a result, it was found that the level of satisfaction of basic psychological needs and the type of academic motivation is associated with a different level of alienation from study. Based on the data obtained, a cluster analysis was carried out, which allowed us to distinguish three main groups of students studying at the university. It was found that these groups differ in the level of expression of basic psychological needs, the type of academic motivation and the degree of feeling of alienation from study.